Horizontal Spatial Transformation of Home-Based Enterprises in Kampung Karangasem, Depok, Sleman - Luluk Rani Puspita; Dwita Hadi Rahmi (Journal of Architectural Research and Design Studies, 2019)
The number of educational facilities around campus is directly proportional to the number of students, especially those from out of town. The emergence of student facilities accommodated by the kampong (villages) around the university can be observed in Kampung Karangasem, Depok, Sleman. This phenomenon led to the concept of Home-Based Enterprises (HBE), which refers to residences transformed into business places. One of the ways to transform a house into HBE is by maximizing the space or land area horizontally without increasing the number of floors. In regard to that, this research aimed to study the horizontal spatial transformation in HBE in Kampung Karangasem. This study used the qualitative deductive approach with case study method. The findings reveal that the transformation of horizontal space involves the extending of space, sharing of space, shifting of space, and squishing of space.Keyword: Spatial Transformation, Horizontal Transformation, Home-based enterprises